Numerical Investigation on Dynamic Performance of a Bridge-Tunnel Transition Section with a Deep Buried Pile-Plank Structure - Shuanglong Li; Limin Wei; Xiaobin Chen; Qun He (Advances in Civil Engineering)
To address the track irregularity at transition zones between subgrade and rigid structures (bridge, tunnel, etc.), some common transition approaches, such as trapezoid subgrade, were adopted in many engineering areas. However, in regard to a mountainous area, the common transition approaches may not be practicable anymore due to the limitation of the length between subgrade and rigid structures. In this paper, a new type of bridge-tunnel transition section with a deeply buried pile-plank structure (DBPPS) for short-distance transition is introduced. A three-dimensional finite element model that considers vehicle-track-subgrade coupling vibration is proposed to study the dynamic performances of a DBPPS transition section in the Shanghai–Kunming high-speed railway. With this model that has been validated with measured responses from field tests, the dynamic responses and the smoothness in track stiffness along the transition zone are analyzed. In addition, the influences of train speed, axle load, and train direction on dynamic responses are investigated, and the influences of two optimization strategies, including varying-length piles and constant-length piles, on the stiffness smoothness of the DBPPS transition section are discussed. Results show that the vibration level of the DBPPS transition section is lower than that of the abutment and the tunnel, and the additional load caused by vertical track stiffness difference aggravates the vibration at the connections between the DBPPS transition section and the abutment (or tunnel). Furthermore, the smoothness in stiffness along the transition zone can be significantly improved by the improvement strategy with varying-length piles.